Pengaruh Dukungan Teman Sebaya Terhadap Stres Akademik pada Mahasiswa Baru - Mumtaza, Yumna; Safitri, Lailatul Norma; Raddina, Maysa Ayu; Husna, Faidatul (CV. Lentera Literasi Indonesia, 2025)
New students have to face greater academic demands in the world of college. The inability to face various academic tasks causes them to experience academic stress. This quantitative study aims to obtain information related to the influence of peer social support on academic stress experienced by new students of the Faculty of Psychology, UIN Malang. This study involved 101 students as research respondents. Peer support and academic stress data were collected through a questionnaire in the form of a google form using a simple random sampling technique. The data obtained were then analyzed using a correlation test using SPSS 26.0 version for windows. The results showed a correlation value (r) of -0.320 with a significance of p = 0.001 (p <0.05). It can be concluded that there is a negative relationship between peer social support and academic stress in new students of the Faculty of Psychology, UIN Malang, although the level of correlation between the two variables is low. Following up on the findings in this study, it is necessary to explore other variables that can influence academic stress in new students, besides peer support.